The early-time dynamics of Rayleigh-Taylor mixing with a premixed layer. (30th October 2021) - Song, Yang; Wang, Pei; Wang, Lili; Ma, Dongjun; He, Anmin; Chen, Dawei; Fan, Zhengfeng; Ma, Zongqiang; Wang, Jianguo
Highlights: In this paper, the early-time dynamics of Rayleigh-Taylor mixing with a premixed density gradient layer was investigated. It was found that the mixing layer undergoes an inactive stage at the early time. The dynamics of instability at this stage is different from the classic Rayleigh-Taylor instability. The influence of initial condition was also investigated in detail. It was found that the amplitude of initial perturbations and the width of premixed layer are important for determining the characteristic time scale of the inactive stage, while the wave number seems to have less effect. Abstract: The early-time dynamics of Rayleigh-Taylor instability with a premixed density gradient layer was investigated by three-dimensional implicit large eddy simulation. Compared with the classic Rayleigh-Taylor instability, it was found that the mixing layer undergoes an inactive stage when the mixing width of the layer is nearly unchanged. The development of hydrodynamic instability with a premixed layer was studied. Energy transfer and vortex generation at the early time show that span-wise vortices predominate at this stage. Afterwards, initial conditions including the parameters of initial perturbations and the mixing width of premixed layer were investigated in detail. In our study, it was found that the amplitude of initial perturbations and the width of premixed layer are important for determining the characteristic time scale of the inactive stage while the wave number has less effect. The influence of initial conditions on the early-time dynamics of mixing layer was also analysed.